Improving Public Access to COVID-19 Pandemic Data in Indonesia for Better Public Health Response - Januraga, Pande Putu; Harjana, Ngakan Putu Anom (Frontiers in Public Health, 2020)
Globalization and the mobility of the world's population have contributed to the coronavirus disease 2019 (COVID-19) pandemic that has rapidly crossed national borders. Experience shows that it is necessary to manage the data and information on the development of outbreaks before, during, and after a pandemic to aid in developing evidence-based health strategies to tackle such outbreaks. However, in dealing with the COVID-19 pandemic, the government of Indonesia does not appear to have optimally managed and utilized the available data. Seemingly improvised data management and limited access to COVID-19 data, which could be further analyzed by researchers, has resulted in a lack of information that would have helped understand the development of the pandemic and inform Indonesia’s scientific responses. Ultimately, Indonesia will lose out in identifying long-term lessons from the COVID-19 pandemic if it does not improve its data management protocols, especially in terms of information disclosure to the public and academia.